ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШАРИЯР»ДАҒЫ ШАҢАРАҚ ТӘЛИМ-ТӘРБИЯСЫ ҲАҚҚЫНДА ЭТНОПЕДАГОГИКАЛЫҚ КӨЗҚАРАСЛАР - Алламбергенов, Е.К. (FAN va JAMIYAT, 2020)
National values play a great role in the education of well-developed, freely-thinking personality, in the spiritual and physical development of young generation. Folk eposes are very important in teaching the youth the best human qualities. Every word, event, heroes’ images in eposes reflect the content of education and upbringing and they also give information about ethnopedagogical point’ of view. The article deals with the issues of education and upbringing in a family on the example of the analysis of the Karakalpak folk epos «Shariyar».